Personalising Climate Change on Instagram: Self-presentation, authenticity, and emotion - Haastrup, Helle Kannik (MedieKultur: Journal of media and communication research, 2022)
This article is a comparative study of how three Danish climate celebrities – an activist, an influencer, and a politician – personalise climate change on Instagram. They engage in personal storytelling about the issue in a way that is closely connected to their public presentation of self and their choice of visual genres. The theoretical framework combines theories of social media aesthetics and publics (Serafinelli, 2018; Papacharissi, 2015), self-presentation (Marshall, 2010), authenticity (Enli, 2015a; Marwick, 2015), and emotion in political communication (Wahl- Jorgensen, 2019). The method is a qualitative case study comparing the three profiles and their overall curational strategy for addressing climate change through particular visual genres and how their personal storytelling is based on performing authenticity, emotion, and connecting with affective publics. The analysis demonstrates how personalising climate change can be performed as coping with climate anxiety, feel-good sustainable consumption, or enthusiastic promotion of Danish green solutions.